Organisational context and behavioural complexity affecting ambidextrous behaviours among SMEs - Poon, Eugene Wai Chuen *; Mohamad, Osman (Elsevier, 2020)
Purpose – The purpose of this paper is to examine the antecedents of exploitative and explorative behaviours and to give valuable insight into the role of ambidextrous behaviours in developing creativity and innovativeness among owner-managers in SMEs. Design/methodology/approach – A review of existing literature was carried out and drawing upon ownermanagers, a survey using structured questionnaires was carried out with a total of 183 useful responses received. The proposed model was analysed using SmartPLS v2.3.7. Findings – The empirical result suggests that behavioural complexity and organisational flexibility encourages exploitative and explorative behaviours, while ambidextrous behaviours encourage creativity and innovativeness. Rigidity, on the other hand, hinders the cultivation of ambidextrous behaviours. Originality/value – The paper entails useful implication by demonstrating that flexibility enables ownermanagers to reconcile competing demands and consequently, cultivate innovative outcomes. In this regard, business owner-managers must learn implicitly how to juggle these contradictory demands, suggesting an internal balancing mechanism independent of the organisational context and individual behavioural complexity. This paper suggests that cultivation of exploitative and explorative behaviours among ownermanagers is useful in encouraging ambidextrous behaviours among SMEs.